IMPLEMENTASI PRINSIP EKONOMI SYARIAH DALAM FATWA DSN-MUI NO.146 TENTANG ONLINE SHOP : SEBUAH STUDI LITERATUR - Kamalia Sani (LA RIBA: Jurnal Perbankan Syariah, 2025)
Abstract This study is a literature review that aims to analyze the substance and implications of DSN-MUI Fatwa No. 146/DSN-MUI/XII/2021 regarding online shopping practices from an Islamic economic perspective. Through an in-depth examination of the official fatwa document and various relevant academic sources, this research maps the Sharia principles underlying digital transactions, identifies practical challenges in implementation, and explores opportunities to strengthen the Sharia-based e-commerce ecosystem in Indonesia. The findings reveal that the fatwa provides a comprehensive normative framework for online trading activities, emphasizing the values of transparency, justice, product halalness, and consumer protection. The consistent application of these principles can enhance ethical governance in the digital economy in accordance with Islamic law. In addition, this study offers several policy recommendations and strategic initiatives for business actors, regulators, and Islamic financial institutions to promote the sustainable implementation of Sharia principles within the digital commerce sector.